Intercorrelation between Financial Inclusion and Poverty: Research Advances using A Bibliometric Analysis - Nur Juaini Fazarina, Julaihi; Azilawati, Banchit; Zakaria, Boulanouar; Josephine, Yau Tan Hwang; Ahmad Dasuki, Abdul Majid (2023)
Research on the financial system's accessibility and its relationship with poverty has gained significant attention since the early 2000s. The term "financial inclusion" has been widely used among researchers and scholars to investigate further the impact of financial access on various dimensions, including poverty reduction and economic inequality. Thus, this study aims to analyse the scientific literature published on financial inclusion and poverty using a bibliometric approach. Scopus database was utilized to collect all literature in this area. Publish, and Perish Software incorporated the obtained data and generated bibliometric indicators such as publication outputs, citation counts, keyword analysis, and collaboration patterns. Microsoft Excel was employed for data analysis. The growth of publications, research productivity, and citation analysis were presented using standard bibliometric analysis. The search revealed a considerable increase in publications, a total of 614 documents over the past 17 years, from 2007 to 2023. Primarily published journals, conference papers, and books, mainly in English and were in Economics, Econometrics and Finance, Social Sciences, and Business, Management and Accounting fields. Furthermore, the analysis identified key themes and trends in this area, highlighting the focus on understanding the relationship between financial inclusion and poverty reduction.